Temporal heterogeneity of the root microbiome in Panax ginseng soils across ecological compartments under mild soil disturbance - Shi, Zhenting; Yang, Limin; Yang, Meiling; Li, Kexin; Yang, Li; Han, Mei (Frontiers in Microbiology, 2024)
Introduction: Knowledge on spatiotemporal heterogeneity of plant root microbiomes is lacking. The diversity of the root microbiome must be revealed for understanding plant-microbe interactions and the regulation of functionally crucial microbial taxa.We here investigated the dynamics of microbial group characteristics within each soil ecological compartment (rhizoplane (B), rhizosphere (J), and bulk soil (T)) across different cultivation years (year 4: F4 and year 5: F5) by using high-throughput sequencing (16S and ITS).Results: According to the species diversity, microbiome diversity and the ASV (amplified sequence variant) number in the rhizoplane ecotone increased significantly with an increase in the planting years. By contrast, the microbiome diversity of the rhizosphere soil remained relatively stable. PCoA and PERMANOVA analyses revealed that microbial taxa among different planting years and ecological compartments varied significantly. Planting years exerted the least effect on the rhizosphere microbiome, but their impact on fungi in the rhizoplane and bacteria in the bulk soil was the most significant.Discussion: Planting years influenced the microbial community composition in various ecological compartments of ginseng root soil. Potentially harmful fungi such as Cryptococcus (2.83%), Neonectria (0.89%), llyonectria (0.56%), Gibberella (0.41%), Piloderma (4.44%), and Plectosphaerella (3.88%) were enriched in F5B with an increase in planting years, whereas the abundance of potentially beneficial Mortierella increased. Correlation analysis indicated associations between bacterial taxa and soil pH/S-CAT, and between fungal taxa and soil moisture content/total